2013
DOI: 10.1051/alr/20013044
|View full text |Cite
|
Sign up to set email alerts
|

Fishing strategies, economic performance and management of moored fishing aggregating devices in Guadeloupe

Abstract: -Moored FADs (MFADs) have been a key area for development in Guadeloupe (Lesser Antilles) since the late 1980's. The main objectives underpinning the development of MFADs were to (i) reduce fishing pressure on coastal fishing resources; (ii) boost fishermen's incomes; and (iii) increase local consumption of locally generated fishery products as a proportion of overall consumption. This paper gives an overview of the current structure of Guadeloupe's fishing fleet and fisheries, with a specific focus on MFAD fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In Guadeloupe, Guyader et al (2013) found that five FAD fleet segments and their involvement in FAD fisheries were highly dependent on harbour-FAD proximity in an attempt to minimize cost and maximize ease of access. Here, only 7 vessels were detected moving longitudinally between FAD B and D (9.24 km) on the same day, yet no vessels were detected moving between FAD F and FAD D or B.…”
Section: Movementsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Guadeloupe, Guyader et al (2013) found that five FAD fleet segments and their involvement in FAD fisheries were highly dependent on harbour-FAD proximity in an attempt to minimize cost and maximize ease of access. Here, only 7 vessels were detected moving longitudinally between FAD B and D (9.24 km) on the same day, yet no vessels were detected moving between FAD F and FAD D or B.…”
Section: Movementsmentioning
confidence: 99%
“…maximize catch of locally sourced seafood (commercial sector; early am); maximize the opportunity of catching billfish (charter fleet; late am to sunset); and maximize fishing opportunities (recreational fleet; late am to sunset)]. This could take the form of separate licensing by sector and allocating specific fishing days and times based on the type of licence purchased (Guyader et al 2013). Another option that may help increase FAD productivity is to limit daytime fishing activity to early afternoon (e.g.…”
Section: Management and Future Research Prioritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the information on the location and density of MFADs is essential for the management of these devices because they influence individual effectiveness. In high densities, MFADs fish aggregation capacity of each float decreases (Holland et al 1990;Cayré, 1991;Dagorn et al 2000), thereby reducing the net benefits of such devices (Guyader et al 2013). In open access fishing contexts, conflicts can arise between MFAD fishers when densities are high.…”
Section: Introductionmentioning
confidence: 99%
“…An aerial survey carried out in 2012 around Guadeloupe to estimate MFADs numbers found high densities of MFADs compared with previously reported densities in this area, especially around the northeastern coasts of Guadeloupe off the La Désirade Island (Guyader et al 2017). According to Guyader et al (2013), there is no effective MFAD management system nor are there any specific formal rights known associated with territorial usage in this fishery. Because MFAD deployment is not managed, fishers continue to install private MFADs and claim space around them, a reason why informal territories may arise (Christy 2000).…”
Section: Introductionmentioning
confidence: 99%